COSA Minutes, June 2016 - Council on Staff Affairs, Valdosta State University (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 2016)
COSA Minutes, June 2016.
1 electronic record. Council on Staff Affairs (COSA), Minutes, June 21, 2016. 1 pages.
Keywords: Council on Staff Affairs (Valdosta State University); Minutes (Records); Committees; Electronic records; Valdosta State University